Центральная предельная теорема для специальных классов функций от эргодических цепей - Москальцова, Н.В.; Шуренков, В.М. (Український математичний журнал, 1994)
The central limit theorem for L-finite bounded functions of ergodic Markov chains is proved. Two useful corollaries are given.